(untitled) (Nigerian Journal of Technology, 2018)
This paper presents an experimental study on workability and compressive strength of concrete using various combinations of lateritic sand and quarry sand as complete replacement for conventional river sand fine aggregate. Quantity of lateritic sand varied from 0 to 50% against quarry dust at interval of 10%. Concrete cubes were prepared for two mix ratios: 1:1.5:3 and 1:2:4 and three water/cement ratios: 0.5, 0.6 and 0.7 and were cured and tested in the laboratory for compressive strength. Slump tests were also carried out for each mix. For each mix and water/cement ratios, control samples were also prepared using river sand as fine aggregate. The resulting concrete cubes fall within the range for normal weight concrete and although laterized quarry dust concrete had poorer workability, their compressive strength compare favourably with those of conventional concrete. The use of laterized quarry sand concrete for structural members is therefore recommended when laterite content is not more than 50%. http://dx.doi.org/10.4314/njt.v37i3.7